427 Cognitive Function and Catastrophizing in the Adult Deformity Population: Single Center Series of 111 Patients. (April 2023) - Scheer, Justin Kemp; Lui, Austin; Burke, John Frederick; Jedwood, Chloe; Wang, Albert; Wang, Elaina; Catalan, Tony; Chang, Diana; Belfield, Bethany; Thapar, Isabelle Thapar; Safaee, Michael; Lau, Darryl; et al.
Abstract : INTRODUCTION: Baseline cognitive impairment (CI) in adult spinal deformity (ASD) pts is unknown and may affect how they report PROMs/experience pain. Goal of this study was to determine baseline CI prevalence and how it's related to PROMs/pain catastrophizing. METHODS: Single center prospective study. PROMs included the Montreal Cognitive Assessment(MOCA), Pain Catastrophizing Scale (PainCS), back pain numerical score, Oswestry Disability Index(ODI), and Scoliosis Research Society-22 (SRS22) questionnaires. Pts were stratified by normal cognition (MOCA scores 26-30), mild CI (MOCA 18-25), moderate CI (MOCA 10-17) and Severe CI (MOCA <10). PainCS (higher = more catastrophizing) has total scor e(T, max = 52) and 3 subdomains (Rumination [R, max = 16], Magnification [M, max = 12], Helplessness [H, max = 24]). Comparisons were made between pts with normal (NORM) and any type of CI (CI) as well as correlations between MOCA and PROMS. MOCA scores were compared postop. RESULTS: Total 111 pts enrolled (mean age 64.1 ± 9.8 yrs, 57.5% F). Mean baseline MOCA score was 25.0±3.0 (mild CI, range 14-30), 59/111(53.1%) had mild/moderate CI. No severe CI. CI pts had significantly higher mean baseline PainCS-T, PainCS-R, and PainCS-M scores than NORM. CI pts had significantly worse baseline ODI (55.2 ± 15 vs 47.9 ± 14.4, p = 0.02) but better self-reported SRS Mental score (3.3 ± 1 vs 2.7 ± 0.8, p = 0.004) than NORM. Lower baseline MOCA scores significantly correlated with higher baseline ODI(r=-0.24, p=0.015), SRS Mental (r = -0.21, p = 0.037), current back pain (r = -0.26, p=0.006), and PainCS-R (r=-0.38, p<0.001), PainCS-M(r = -0.37, p < 0.001), PainCS-H (r = -0.27, p = 0.004), PainCS-T(r = -0.36, p < 0.001). Mean pre/postop MOCA scores were not significantly different (p > 0.05). CONCLUSIONS: Baseline CI is frequent in ASD pts and associated with higher baseline pain/disability and pain catastrophizing compared to ASD pts with normal cognition. The CI persists postoperatively.